2015
DOI: 10.1557/opl.2015.196
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Performance of Heterogeneous Anode Assemblies of Silicon Nanowires on Carbon Meshes for Lithium-Sulfur Battery Applications

Abstract: Si is a promising anode material for Li storage due to its high theoretical specific capacity surpassing 4200 Ah/kg. Si based anodes exhibit an extreme instability upon electrochemical incorporation of Li given the accompanied large volume expansion of about 400%. We show innovative anode assemblies composed of a forest of free standing Si nanowires conformally integrated on carbon meshes. The morphology of silicon nanowires allows a volume expansion and compression lowering strain incorporation. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…A planar sputtering technique (Gatan) has been used to deposit an Au layer of up to 1 nm thickness on the planar samples. The results of the sputtered Au layers exhibit similar results compared to a previous 3D Au deposition technique (2). The Au nanoparticles as catalyst side for the SiNW growth have been formed in an annealing step after the deposition of an Au layer.…”
Section: Methodssupporting
confidence: 72%
See 1 more Smart Citation
“…A planar sputtering technique (Gatan) has been used to deposit an Au layer of up to 1 nm thickness on the planar samples. The results of the sputtered Au layers exhibit similar results compared to a previous 3D Au deposition technique (2). The Au nanoparticles as catalyst side for the SiNW growth have been formed in an annealing step after the deposition of an Au layer.…”
Section: Methodssupporting
confidence: 72%
“…They are currently integrated in nanoelectronic devices due to the good gate coupling according to their 1-dimensional structure and small diameters of less than 50 nm (1). SiNWs are also currently tested as replacement of metallic lithium as negative electrode in Li ion batteries (2). Si exhibits a large storage capacity of nearly 4000 mAh/g Si accompanied by a volume expansion of more than 400 percent, which hinders the integration as bulky layers in anode stacks.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon is one of the most promising anode materials replacing metallic Li due to a maximum specific capacity of 3579 mAh/g at room temperature 2 but is accompanied by a large volume change upon lithiation and de-lithiation. To overcome stress related fracturing, several Si-based nanostructures 3 that by their intrinsic geometry and neighboring free expansion volume allow an enhanced mechanical stress relaxation, like nanoparticles 4 5 6 , nanowires 7 8 9 10 11 12 13 , microwires 14 and nanotubes 15 16 17 18 , have been studied in battery setups. Further on, prelithiated Si nanostructures allow the insertion of Li independent of the chosen cathode material 6 8 19 20 .…”
mentioning
confidence: 99%
“…As an ideal nanostructure to ensure both the possibility of free expansion and relaxation of Si as well as a good electrical contact to a carbon current collector, pure Si nanowires (SiNWs) have been investigated in half-cell setups as a promising solution to address both issues 12 21 . Recently, the SiNWs are grown by using planar sputtered Au layers to create Au nanoparticles (NPs) on a 3D surface 11 .…”
mentioning
confidence: 99%
“…Excellent research results have been shown in half-cells, but the enhanced cyclability in full cells remains to be shown [9,[134][135][136][137]. Promising results with nanowires directly grown on carbon meshes were recently demonstrated [138]. For full cell operation, also the formation of the solid-electrolyte interface (SEI) at the silicon surface needs to be controlled, in order to tune the electrochemical reactions.…”
Section: Silicon Nanowire Based Sensorsmentioning
confidence: 99%